2022
DOI: 10.3390/v14010090
|View full text |Cite
|
Sign up to set email alerts
|

A Population of CD4+CD8+ Double-Positive T Cells Associated with Risk of Plasma Leakage in Dengue Viral Infection

Abstract: According to the WHO 2009 classification, dengue with warning signs is at the risk of developing severe form of dengue disease. One of the most important warning signs is plasma leakage, which can be a serious complication associated with higher morbidity and mortality. We report that the frequency of CD4+CD8+ double-positive (DP) T cells is significantly increased in patients at risk of developing plasma leakage. Transcriptomic analysis demonstrated that CD4+CD8+ DP cells were distinct from CD4+ Single Positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…However, evidence indicates that in vivo terminally differentiated effector CD4 + may acquire the α-chain of CD8. DP T cells have been higher in HIV ( 34 , 35 ) and other viral infections ( 36 , 37 ) autoimmune and chronic inflammatory disorders ( 38 , 39 ). Here we report significantly higher DP T in chronic SIV infected macaques’ tonsils.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence indicates that in vivo terminally differentiated effector CD4 + may acquire the α-chain of CD8. DP T cells have been higher in HIV ( 34 , 35 ) and other viral infections ( 36 , 37 ) autoimmune and chronic inflammatory disorders ( 38 , 39 ). Here we report significantly higher DP T in chronic SIV infected macaques’ tonsils.…”
Section: Discussionmentioning
confidence: 99%
“…The lymphocyte reference range results of healthy individuals in different countries worldwide present different results associated with ethnic groups, showing the importance of obtaining specific evaluation parameters for different racial patterns. ( 23 , 25 - 29 )…”
Section: Discussionmentioning
confidence: 99%
“…Although we proved the antiviral potentials of DP T cells in our study, the roles of DP T cells during HTNV infection were still need further study. Yu et al identified the DP T cells in Dengue virus infection as a potential marker of plasma leakage progression to shock and may contribute to the pathogenesis of disease [ 23 ]. We also studied the correlation between dynamic changes of DP T cells and clinical indicators of HFRS patients.…”
Section: Discussionmentioning
confidence: 99%
“…During Dengue virus infection, frequency of DP T cells was significantly increased. Instead of against virus, they were believed to contributed to the pathogenesis of plasma leakage [ 23 ]. In rheumatoid arthritis (RA), DP T cells were recognized as inflammatory cells and contributed to disease pathogenesis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%